Canada : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2002)
This report evaluates the Observance of Standards and Codes on the Fiscal Transparency Module for Canada. Fiscal management in Canada meets the requirements of the fiscal transparency code and in a number of instances represents best practice. Recent reforms by federal and provincial governments continue to improve transparency. The federal government has been particularly innovative in the use of private sector economic forecasts, prudence factors, and a contingency reserve in its fiscal forecasts. Canada also deserves high marks for statistical integrity, impartial tax administration, open procurement, and a transparent regulatory process.